Putting in Golf: Is it as easy as it seems to be? / Mazlan Ismail, Santhosh Ayathupady Mohanan and Solha Husin - Ismail, Mazlan; Mohanan, Santhosh Ayathupady; Husin, Solha (Faculty of Sports Science and Recreation, 2013)
This study aims at revealing the specific distance considered hardest to putt and discovering the causal factors from the golfers’ personal opinion. The objectives of this exploratory study are achieved by conducting two separate studies, using the same samples consisting of 153 golfers with ages ranging from 18 to 60 years old. Two putting tests were carried out right before the participants took part in a golfing competition. They were asked to putt only one time from four different distances (3, 6, 12 and 24 feet). The number of strokes taken until a ball sank into a hole indicates the samples’ performance. Next, 10 golfers were randomly approached to take part in the interviews right after the competition. Repeated measures one-way ANOVA results showed there was a significant effect for putting distance, Wilks’ Lambda = .43, F (3, 150) = 74.49, p < 0.05, multivariate eta squared = .57 and the Pairwise comparison revealed 6 feet distance significantly higher (M=2.35, SD=0.62) compared to other distances. The qualitative results disclosed that most of the participants described their psychological states (i.e., anxiety and self-belief) play a big role in influencing their ability to putt. In addition, technically such as the position of the grip and stance alignments are other reasons that make putting in certain distances hardest to execute. In conclusion six feet distance is considered the hardest distance to execute. Meanwhile cognitive, emotional, and behavioural aspects associate for making the distance hardest to perform.